The camel who had the hump - Bright, Rachel,Field, Jim (Orchard Books, 2024)
In the shimmering desert, a joyful herd of camels are out to find an oasis for a drink and a play. All, that is, except Cuthbert. He hasn't woken up in such a good mood. He's hot, he's tired and he certainly WON'T be walking today! There is ABSOLUTELY NOTHING that will get him out of his grump. Or is there? Might the desert's hoppiest, happiest creature be able to help?A gloriously empowering tale of how choosing fun can turn a grumpy, humpy start into a happy ending.
Keywords: Camels; Deserts; Mood (Psychology); Jerboas; Positive psychology; Stories in rhyme; Picture books